2008
DOI: 10.1111/j.1442-9071.2008.01698.x
|View full text |Cite
|
Sign up to set email alerts
|

The one‐eye trial and fellow eye response to prostaglandin analogues

Abstract: One-eye trial is a feasible method to determine the effectiveness of prostaglandin analogues and to predict the amount of IOP reduction in the fellow eye in patients with high tension glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 23 publications
(54 reference statements)
0
14
0
1
Order By: Relevance
“…A retrospective study by Dayanir et al [4] reported that there was a significant correlation of the IOP response in the initial eye (adjusted IOP change) and that of the subsequent eye (unadjusted IOP change) in patients with high tension glaucoma, whereas this relationship was not significant in patients with normal tension glaucoma. Another retrospective study documented that a correlation between the two eyes was higher when using adjusted IOP changes [5].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study by Dayanir et al [4] reported that there was a significant correlation of the IOP response in the initial eye (adjusted IOP change) and that of the subsequent eye (unadjusted IOP change) in patients with high tension glaucoma, whereas this relationship was not significant in patients with normal tension glaucoma. Another retrospective study documented that a correlation between the two eyes was higher when using adjusted IOP changes [5].…”
Section: Discussionmentioning
confidence: 99%
“…If office hours diurnal IOP measurements was judged to be high for the patient then glaucoma medications were started as for any open angle glaucoma patient. 7 At the last follow-up, an IOP ≤18 mmHg without any antiglaucoma drops was considered as a complete success, an IOP ≤18 mmHg with one or more antiglaucoma drops was considered as a qualified success and an IOP >18 mmHg despite antiglaucoma drops or need for glaucoma surgery was considered as a failure.…”
Section: Methodsmentioning
confidence: 99%
“…So nuç lar: APAKG'da son preoperatif değerlendirmedeki ortalama İOB (%95 CI), antiglokomatöz ilaç sayısı ve Snellen görme keskinliği 30,9±15,6 mmHg (23,0-38,0), 2,6±1,4 kutu ve 0,4±0,2 sıradan son takipte 15,5±3,9mm Hg (p<0,000, 13,8-17,0), 0,6±0,9 (p<0,000) kutu ve 0,6±0,3 (p=0.001) sıra olarak değişti. KPAKG'da son preoperatif değerlendirmedeki aynı parametreler 18, 0±7,8 mmHg (15,[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]8), 1,6±1,1 kutu ve 0,5±0,2 sıradan son takipte 14, 7±3,6 mmHg (p<0,023,13,[4][5][6][7][8][9][10][11][12][13][14][15][16]0), 0,5±0,8 (p<0,000) kutu ve 0,6±0,3 (p=0,007) sıra olarak değişti. APAKG ve KPAKG'u için ortalama takip süresi (95% CI) sırasıyla 554±646 (268-841) ve 747±820 (438-1041) gün idi.…”
unclassified
“…However, a recent study demonstrates the lack of correlation between IOP responses of fellow eyes to the same medication in a one-eye trial [4]. Some studies demonstrate that one-eye trials predict the amount of IOP reduction in the fellow eye only in high-tension glaucoma or in glaucoma suspects [5,6]. The results evaluating the use of one-eye trials have been varied, and the selection of subjects and methods of one-eye trials still need to be refined.…”
Section: Introductionmentioning
confidence: 96%